Pengaruh Stabilitas Keuangan, Pengawasan, Dan Kualitas Auditor Kecurangan Laporan Keuangan Sektor Industri Pada Bursa Efek Indonesia (BEI) - Dio Jeremia Sembiring; Seprianto Purba; Shaila Pratika Sari; Stephanie Imaylia Napitupulu; An Suci Azzahra (CV. ITTC INDONESIA, 2025)
This study aims to analyze the influence of financial stability, ineffective monitoring, and auditor quality on financial statement fraud in processed food sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The research uses a quantitative approach with a causal associative design. The sample consists of 16 companies with a total of 48 observations. Data were analyzed using multiple linear regression with SPSS 25. The t-test results show that all three independent variables significantly affect financial statement fraud with significance values as follows: financial stability (t = 4.648; sig. = 0.000), ineffective monitoring (t = 51.836; sig. = 0.000), and auditor quality (t = 7.135; sig. = 0.000). The F-test result shows an F value of 6142.986 with a significance level of 0.000, indicating that the regression model is highly significant in predicting financial statement fraud. Based on these findings, it is recommended that companies strengthen internal oversight, select high-quality auditors, and maintain financial stability to minimize potential fraud that could harm stakeholders.